Automated analyses of dried blood spots collected by volumetric microsampling devices - Dvořák, Miloš; Kubáň, Pavel (Analytica chimica acta, 2024)
BACKGROUND: Dried blood spot (DBS) sampling on cellulose cards suffers from varying blood haematocrit levels and from chromatographic effects, which have a direct impact on quantitative DBS analyses. Commercial volumetric microsampling devices were, therefore, introduced to mitigate these effects, however, these devices are not compatible with automated DBS processing systems and must be processed manually. RESULTS: Capillary electrophoresis (CE) instruments use fused-silica (FS) capillaries for precise and accurate liquid handling as well as for injection, separation, and quantitative analyses of liquid samples. These inherent features of an Agilent 7100 CE instrument were employed for the automated processing (elution and homogenization) of DBSs collected by hemaPEN® volumetric devices (2.74 μL of capillary blood per spot). The hemaPEN® samples were processed directly in CE vials by consecutive transfers of 56 μL of methanol and 14 μL of deionized water through the FS capillary in a sequence of 39 DBSs with repeatability of the liquid transfers better than 1.4 %. The resulting DBS eluates were homogenized by a quick air flush through the capillary and analyzed by the same capillary and CE instrument. Creatinine was selected as a clinically relevant model analyte and its endogenous concentrations in DBSs were determined by CE with capacitively coupled contactless conductivity detection (CE-C4D) in a background electrolyte solution consisting of 50 mM acetic acid and 0.1 % (v/v) Tween 20 (pH 3.0). The overall repeatability of the automated DBS processing and CE-C4D analyses of 39 DBSs was ≤7.1 % (peak areas) and ≤0.6 % (migration times), the calibration curve was linear in the 25-500 μM range (R2 = 0.9993) and covered all endogenous blood creatinine levels, the limit of detection was 5.0 μM, and sample throughput was >12 DBSs per hour. DBS ageing for 60 days and varying blood haematocrit levels (20-70 %) did not affect creatinine quantitative results (≤6.9 % for peak areas). Inter-capillary and inter-instrument repeatability was ≤7.7 % (peak areas) and ≤3.4 % (migration times) and demonstrated an excellent transferability of the proposed analytical concept among laboratories. SIGNIFICANCE AND NOVELTY: This contribution is the first-ever report on the use of a single off-the-shelf analytical instrument for fully automated analyses of DBSs collected by commercial volumetric microsampling devices and holds great promise for future unmanned quantitative DBS analyses.
Keywords: Dried blood spot; elektroforéza kapilární; Automation; Volumetric microsampling; Capillary electrophoresis; Capacitively coupled contactless conductivity detection; Electrophoresis, Capillary; lidé; Humans; Creatinine; automatizace; test suché kapky krve; Dried Blood Spot Testing; kreatinin